2011
DOI: 10.4049/jimmunol.1003332
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and the Regulation of Placental Inflammation

Abstract: The vitamin D-activating enzyme 1α-hydroxylase (CYP27B1) and vitamin D receptor (VDR) support anti-inflammatory responses to vitamin D in many tissues. Given the high basal expression of CYP27B1 and VDR in trophoblastic cells from the placenta, we hypothesized that anti-inflammatory effects of vitamin D may be particularly important in this organ. Pregnant wild type (WT) mice i.p. injected with LPS showed elevated expression of mouse Cyp27b1 (4-fold) and VDR (6-fold). Similar results were also obtained after e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
120
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(129 citation statements)
references
References 54 publications
1
120
0
8
Order By: Relevance
“…A recent study revealed that early pregnancy vitamin D status is associated with some inflammatory biomarkers in mid-pregnancy [23]. In a recent animal study, researchers showed that maternal VDD leads to aberrant inflammatory responses in the fetus [24]. Preeclampsia is the most extreme point of systemic inflammatory response and offers a good opportunity to assess the inflammatory process in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that early pregnancy vitamin D status is associated with some inflammatory biomarkers in mid-pregnancy [23]. In a recent animal study, researchers showed that maternal VDD leads to aberrant inflammatory responses in the fetus [24]. Preeclampsia is the most extreme point of systemic inflammatory response and offers a good opportunity to assess the inflammatory process in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of a normal pregnancy requires efficient coordination of antimicrobial and anti-inflammatory responses within the feto-placental unit. Vitamin D plays a significant role in modulating both of these processes, thereby helping to maintain a pregnancy [20]. The Taq1, Bsm1, and Apa1 polymorphisms of the VDR gene may affect mRNA stability leading to a change in protein levels and an imbalance between the Th1 and Th2 related cytokines, which is crucial in determining the clinical outcome of preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…Недавнее ретро-спективное исследование показало, что негативный эффект дефицита витамина D опосредуется через эндометрий, но корреляции уровня дефицита с харак-теристиками стимуляции яичников или маркерами качества эмбриона обнаружено не было [8]. Несколько когортных исследований попытались оценить значения уровней витамина D у пациенток с бесплодием [8][9][10][11][12]. Результаты этих исследований противоречивы: некото-рые данные показывают, что дефицит витамина D ассо-циирован со снижением частоты наступления бере-менности [8,10], другие не находят связи D-дефицита с конечными репродуктивными исходами [11,12].…”
Section: рисунок 2 эффекты витамина Dunclassified
“…Несколько когортных исследований попытались оценить значения уровней витамина D у пациенток с бесплодием [8][9][10][11][12]. Результаты этих исследований противоречивы: некото-рые данные показывают, что дефицит витамина D ассо-циирован со снижением частоты наступления бере-менности [8,10], другие не находят связи D-дефицита с конечными репродуктивными исходами [11,12]. Следует сказать, что число пациентов, включенных в эти исследования, мало, и в протоколах не соблюда-лась политика переноса одного эмбриона (осущест-влялся перенос до 4 эмбрионов, что могло существен-но повлиять на исходы).…”
Section: рисунок 2 эффекты витамина Dunclassified